Emerging Variability in HIV-1 Genetics among Recently Infected Individuals in Yunnan, China - Chen, Min (Public Library of Science, 2013)
BACKGROUND: Yunnan has the longest endured Human Immunodeficiency Virus-1 (HIV-1) epidemic in China, and the genetic diversity of HIV-1 constitutes an essential characteristic of molecular epidemiology in this region. To obtain a more comprehensive picture of the dynamic changes in Yunnan’s HIV-1 epidemic, a cross-sectional molecular epidemiological investigation was carried out among recently infected individuals. METHODOLOGY/PRINCIPAL FINDINGS: We sequenced partial gag (HXB2∶781–1861) and env (HXB2∶7002–7541) genes from 308 plasma samples of recently infected patients. With phylogenetic analysis, 130 specimens generated interpretable genotyping data. We found that the circulating genotypes included: CRF08_BC (40.8%), unique recombinant forms (URFs, 27.7%), CRF01_AE (18.5%), CRF07_BC (9.2%), subtype B (2.3%) and C (1.5%). CRF08_BC was the most common genotype, and was predominant in both intravenous drug users (IDUs) and heterosexually transmitted populations. CRF08_BC and CRF07_BC still predominated in eastern Yunnan, but CRF08_BC showed increasing prevalence in western Yunnan. Strikingly, the URFs raised dramatically in most regions of Yunnan. Seven different types of URFs were detected from 12 prefectures, suggesting that complicated and frequent recombination is a salient feature of Yunnan’s HIV-1 epidemic. Among URFs, two BC clusters with distinctive recombination patterns might be potential new CRF_BCs. CRF01_AE was no longer confined to the prefectures bordering Myanmar, and had spread to the eastern part of Yunnan, especially the capital city of Kunming, with a large number of infections in the transient population. The ratios of the main genotypes showed no statistical differences between infected IDUs and heterosexually transmitted infections. CONCLUSIONS/SIGNIFICANCE: The changing patterns of the dominant HIV-1 genotypes in Yunnan indicate the complex evolving dynamic nature of the epidemic. Understanding new trends in molecular epidemiology of HIV-1 infection is critical for adjusting current prevention strategies and vaccine development in Yunnan.